The Three Paradoxes of Roland Barthes - Lombardo, Patrizia (Book collections on Project MUSE., 1989)
In the field of contemporary literary studies, Roland Barthes remains an inestimably influential figure-perhaps more influential in America than in his native France. The Three Paradoxes of Roland Barthes proposes a new method of viewing Barthes's critical enterprise. Patrizia Lombardo, who studied with Barthes, rejects an absolutist or developmental assessment of his career. Insisting that his world can best be understood in terms of the paradoxes he perceived in the very activity of writing, Lombardo similarly sees in Barthes the crucial ambiguity that determines the modern writer-an irresis.